Prediction of the Mechanisms by Which Quercetin Enhances Cisplatin Action in Cervical Cancer: A Network Pharmacology Study and Experimental Validation - Ji, Huihui; Li, Kehan; Xu, Wenbin; Li, Ruyi; Xie, Shangdan; Zhu, Xueqiong (Frontiers in Oncology, 2022)
Yimucao has been used as an herbal medicine to treat gynecological diseases. Common genes of Yimucao active compounds were investigated through network pharmacology. The components and targets of Yimucao were retrieved from TCMSP database. Cervical cancer targets were collected via GeneCards, TTD, DisGeNET, and KEGG. Cisplatin-related genes were downloaded from GeneWeaver. Protein-protein interaction (PPI) network was confirmed using the STRING database. Drug-bioactive compound-disease-target network was constructed with Cytoscape. GO and KEGG analyses were performed to investigate common targets of quercetin and cisplatin in cervical cancer. We found quercetin was the most bioactive compound of Yimucao. The drug-bioactive compound-disease-target network contained 93 nodes and 261 edges. Drug related key targets were identified, including EGFR, IL6, CASP3, VEGFA, MYC, CCND1, ERBB2, FOS, PPARG, CASP8. Core targets were mainly about response to metal ion, cellular response to xenobiotic stimulus, and transcription factor complex. The KEGG pathway analysis revealed that quercetin and cisplatin may affect cervical cancer through platinum drug resistance, p53 and HIF-1 pathways. Furthermore, quercetin plus cisplatin down-regulated the expression of EGFR, MYC, CCND1, ERBB2 proteins and up-regulate CASP8 expression in HeLa and SiHa cells. Functionally, quercetin enhanced cisplatin-induced anticancer activity in cervical cancer cells. Our results clarify that quercetin can be used to overcome cisplatin resistance in cervical cancer cells.